The longyearbyen CO2 lab project:Lessons learned from a decade of characterizing an unconventional reservoir-caprock system - Olaussen, S.; Senger, K.; Birchall, T.; Braathen, A.; Grundvåg, S.; Hammer; Koevoets, M.; Larsen, L.; Mulrooney, M.; Mørk, M. B.; Ogata, K.; Ohm, S.; et al. (Proceedings, Fifth CO2 Geological Storage Workshop, 2018)
The UNIS CO2 Lab has evaluated the subsurface near the local coal-fueled power plant in Longyearbyen, Svalbard, Norway as a possible CO2 storage site. Extensive geological and pressure studies, including eight fully cored slim boreholes have proven a nearly 400 m thick shale dominated unit as an efficient cap rock for buoyant fluids. The underlying 300 m thick fractured and under-pressured heterolithic succession is identified as a potential unconventional reservoir The study concludes that the reservoir exhibits injectivity and storage capacity that are sufficient for the relative small volume of the CO2 emitted from the coal power plant.